2006
DOI: 10.1007/s10722-004-3227-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity in AA and CC Genome Oryza Species in Southern South Asia

Abstract: The CC genome of Oryza is found in nine species of Oryza that are distributed on all continents having a tropical climate. Three diploid Oryza species with CC genome are found in Africa and Asia to Papua New Guinea. In southern South Asia these three CC genome diploid species can be found, O. eichingeri and O. rhizomatis in Sri Lanka and O. officinalis in India. AA genome wild relatives of rice are also found in the same geographic region. Germplasm of both diploid CC and AA genome Oryza germplasm has recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…The relationships among the three diploid species with the C‐genome type have been investigated intensively using different genetic markers. Different results were produced, favoring either the relationship between O. officinalis and O. rhizomatis (Shcherban et al, 2000a, 2000b; Bao & Ge, 2004; Zou et al, 2008; Wang et al, 2009) or between O. eichingeri and O. rhizomatis (Bao et al, 2006; Bautista et al, 2006; Zhang & Ge, 2007). With a much larger dataset of 68 genes and the inclusion of additional samples of O. eichingeri from Africa, we obtained a fully resolved phylogeny of the C‐genome diploid species.…”
Section: Discussionmentioning
confidence: 99%
“…The relationships among the three diploid species with the C‐genome type have been investigated intensively using different genetic markers. Different results were produced, favoring either the relationship between O. officinalis and O. rhizomatis (Shcherban et al, 2000a, 2000b; Bao & Ge, 2004; Zou et al, 2008; Wang et al, 2009) or between O. eichingeri and O. rhizomatis (Bao et al, 2006; Bautista et al, 2006; Zhang & Ge, 2007). With a much larger dataset of 68 genes and the inclusion of additional samples of O. eichingeri from Africa, we obtained a fully resolved phylogeny of the C‐genome diploid species.…”
Section: Discussionmentioning
confidence: 99%
“…, 2006; Lin et al. , 2007), Rc gene governs the pericarp colour of seeds (Bautista et al. , 2006; Konishi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Our present result indicates that gene flow may exist between O. eichingeri and O. rhizomaits in Sri Lanka to some extent. The result consists with the study by Bautista et al (2006). Using RAPD and SSR markers, Bautista et al (2006) studied the genetic diversity of A-and C-genome species in southern South Asia and found that one O. rhizomatis accession clustered with the O. eichingeri accessions.…”
Section: Relationships Among Species and Speciation Of The Aiiotetrapmentioning
confidence: 89%
“…The result consists with the study by Bautista et al (2006). Using RAPD and SSR markers, Bautista et al (2006) studied the genetic diversity of A-and C-genome species in southern South Asia and found that one O. rhizomatis accession clustered with the O. eichingeri accessions. Nevertheless, further investigations using multiple approaches are needed to clarify the genetic relationships between the two species and verify the taxonomic status of the two races of O. eichingeri.…”
Section: Relationships Among Species and Speciation Of The Aiiotetrapmentioning
confidence: 89%
See 1 more Smart Citation